PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) ELEKTRONIK BERBASIS KETERAMPILAN BERPIKIR KRITIS MELALUI METODE KASUS PADA MATERI SISTEM PENCERNAAN (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce Electronic Student Worksheets (LKPD) Based on Critical Thinking Skills Through Case Methods on Digestive System Materials for class XI high school. This research was carried out at the Biology Education Study Program, Faculty of Education, Riau University and SMA Negeri 1 Kampar Kiri Hilir from November 2021 to March 2022. The research subject was KD 3.6 material on the food digestive system in class XI SMA. The type of research used is the ADDIE Research and Development model. The instruments used are in the form of validation sheets and response questionnaires. the validation sheet consists of 3 aspects, namely the design aspect, the pedagogic aspect, and the content feasibility aspect. the average results of the validation of the electronic LKPD based on these three aspects are 3.79, 3.83, and 3.93, respectively, with an average overall score of 3.85 in the very valid category. the results of the limited trial phase I got an average score of 3.74 with a very good category. while the results of the second phase of the trial got an average score of 3.53 with a very good category. The results of the study show that the electronic worksheets based on critical thinking skills through the case method on the digestive system material for class XI are of high quality and are suitable to be used as learning resources.Key Words: Electronic LKPD, Critical Thinking, Case Method, Digestive System